2018
DOI: 10.1177/0963662518806451
|View full text |Cite
|
Sign up to set email alerts
|

From engaging publics to engaging knowledges: Enacting “appropriateness” in the Austrian biobank infrastructure

Abstract: While there is consensus on the essential importance of public engagement in further developments of biobanking, the related investigation of public views predominantly focused on the concerns expressed by the publics, and the concrete format of public engagement, without delving into the ways these concerns are constituted. In this paper, we synthetize recent research on public engagement in order to describe the constitution of respective concerns as 'engagement of knowledges'. By shifting from 'publics' to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…On the other hand, many respondents think such information should be provided in ICs (see Table 3). Findings from other quantitative and qualitative studies [5, 30, 31] that address data processing from the perspective of participants and the public, support providing information about data uses since concerns about data protection and potential use of personal data outside the research context influence preferences for consent types and participants’ views of biobank-based research.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, many respondents think such information should be provided in ICs (see Table 3). Findings from other quantitative and qualitative studies [5, 30, 31] that address data processing from the perspective of participants and the public, support providing information about data uses since concerns about data protection and potential use of personal data outside the research context influence preferences for consent types and participants’ views of biobank-based research.…”
Section: Discussionmentioning
confidence: 89%
“…Not only have the number of biobanks multiplied [1, 4] but the understanding of what constitutes a biobank has changed. Defined originally as mere ‘collections of samples and tissues’ [4] and ‘associated data’ [5–8], biobanks have evolved into complex infrastructures, which contribute in important ways to health research and operate at national, regional and global levels [9, 10]. This development, together with current advances in molecular medicine and genomics, has led to ethical, legal and societal implications (ELSI) related to three main areas of concern.…”
Section: Introductionmentioning
confidence: 99%
“…This shift might also—at last—make possible the kind of participant engagement in biobanking that for decades has been called for. Despite many ingenious initiatives, the establishment of participant engagement in biobanking has been like flogging a dead horse (Goisauf and Durnová 2019 ). Again, with hindsight, the reason for this is in plain view: why should anyone engage in an enterprise where someone else makes every decision and takes full responsibility?…”
Section: Discussionmentioning
confidence: 99%
“…It restricts autonomy in decision making as to whether the aims and risks of a new research project are acceptable, though specific limitations can be inbuilt to limit this, particularly by ensuring "oversight and approval of future research activities" and "an ongoing process of providing information" [22]. Research has found that "the more unclear the purpose of the sample and data usage is, the less there is a trust in the 'appropriateness' of research" [24]. The key issue is the ambiguity of 'informed consent'.…”
Section: Biobanking and Informed Consentmentioning
confidence: 99%